Recycled aggregate concrete prepared by using construction solid waste and preparation method thereof
Through the synergistic effect of chemically targeted modification packages and quicklime powder, the pores and microcracks of recycled coarse aggregates are sealed in situ, solving the problems of high water absorption and low strength of recycled aggregates. This achieves the improvement of concrete performance and resource utilization, while avoiding high energy consumption and high pollution.
Patent Information
- Application Number
- CN202610502521.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-16
- Publication Date
- 2026-06-26
AI Technical Summary
Existing technologies suffer from problems such as high water absorption, low strength, and deterioration of concrete workability due to the adhesion of old mortar to the surface of recycled coarse aggregate. Furthermore, traditional pretreatment processes are energy-intensive and highly polluting, making it difficult to achieve low-cost, high-value-added industrial applications.
By employing the synergistic physicochemical effects of chemically targeted modification packages, induced water, and quicklime powder, the pores and microcracks of recycled coarse aggregate are sealed in situ through infiltration, thermal activation, and precipitation expansion stages. Combined with a multi-stage mixing process, this ensures that the chemically modified components fully react inside the recycled aggregate, forming a dense crystalline phase, thereby improving aggregate strength and stabilizing the hydration process.
It effectively reduces the water absorption rate of recycled aggregates, improves the mechanical properties of concrete, avoids high energy consumption and high pollution, ensures the workability and structural stability of concrete, and provides an efficient and reliable path for the resource utilization of construction solid waste.
Smart Images

Figure CN122277186A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a recycled aggregate concrete prepared from construction solid waste and its preparation method. Background Technology
[0002] With the continuous advancement of urbanization, the amount of construction waste is increasing dramatically, with waste concrete accounting for a large proportion. Crushing and screening waste concrete and then using it as recycled coarse aggregate in the preparation of new concrete is an important way to realize the resource utilization of construction solid waste and alleviate the shortage of natural sand and gravel resources.
[0003] However, recycled coarse aggregates obtained by directly crushing waste building concrete typically have a large amount of loose and porous old mortar adhering to their surface. This old mortar contains well-developed microcracks and numerous pore defects, giving the recycled aggregates a natural disadvantage of extremely high water absorption and low structural strength. When this untreated recycled aggregate is used directly to prepare new concrete, its strong water absorption characteristics cause it to rapidly and significantly draw away conventional mixing water in the initial mixing stage, resulting in a drastic loss of slump in the concrete mixture and severely damaging the overall workability of the concrete. Simultaneously, some conventional techniques attempt to compensate by directly adding chemical admixtures during the mixing stage, but these undirected and uncured modified components are easily released into the matrix, interfering with the normal setting and hydration process of ordinary Portland cement, leading to highly unstable interfacial bonding between the aggregate and the cement gel network. In order to remove these inferior old mortars and improve aggregate quality, existing technologies often rely on high-intensity mechanical grinding and stripping processes or high-concentration strong acid soaking to dissolve the loose surface structure. These complex pretreatment methods not only lead to extremely high energy consumption, but also easily cause serious secondary environmental pollution, resulting in high conversion costs for construction solid waste and making it difficult to achieve low-cost, high-value-added large-scale industrial applications. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a recycled aggregate concrete prepared from construction solid waste and its preparation method. This solves the problems of high water absorption, low strength, and deterioration of concrete workability caused by porous old mortar adhering to the surface of recycled coarse aggregate. At the same time, it avoids the problems of high energy consumption and high pollution of traditional aggregate pretreatment processes.
[0005] To achieve the above objectives, the present invention provides the following technical solution: Firstly, the present invention provides recycled aggregate concrete prepared from construction solid waste, employing the following technical solution: A recycled aggregate concrete prepared using construction solid waste comprises the following raw materials in parts by weight: 350-400 parts of ordinary Portland cement; 1000-1100 parts of recycled coarse aggregate; 600-700 parts of natural fine sand; 15-22 parts of chemically targeted modification package; 15-20 parts of quicklime powder; 30-44 parts of inducing water; and 150-170 parts of conventional mixing water.
[0006] By adopting the above technical solution, this invention utilizes the synergistic physicochemical effects of chemically targeted modification packages, induced water, and quicklime powder to in-situ seal and strengthen the pores and microcracks inside recycled coarse aggregate, thereby reducing the water absorption rate of the aggregate and improving the overall mechanical properties of concrete. The specific reaction process and mechanism are divided into the following steps: Step 1, Solid-Liquid Penetration Stage: After the induced water enters the mixing system, it preferentially wets the surface of the recycled coarse aggregate and penetrates into the microcracks inside. The powder components of the chemically targeted modification package dissolve or form a suspension under the action of the induced water, and penetrate into the interior of the recycled coarse aggregate along with the induced water due to capillary force, adhering to the micropores deep in the old mortar.
[0007] Step Two, Thermal Activation and Sedimentation Expansion Stage: After the quicklime powder is added, it undergoes a hydration reaction with the free water on the surface of the aggregate and in the shallow pores, releasing a large amount of heat and raising the local temperature of the system. Under thermal activation, the chemically targeted modified components that have entered the pores of the aggregate undergo a precipitation reaction and crystallize, generating micro-expanded crystalline precipitates. These precipitates, relying on the volume expansion effect, tightly fill and seal the micropores and cracks of the old mortar, completing the in-situ physical sealing of microscopic defects in the recycled coarse aggregate and reducing the aggregate's own water absorption rate.
[0008] Step 3, Cementing and Curing Stage: The recycled coarse aggregate, which has been strengthened by internal pores, is then mixed with ordinary silicate cement, natural fine sand and conventional mixing water. The ordinary silicate cement undergoes a conventional hydration reaction to form a dense hydrated calcium silicate gel network, which tightly wraps and bonds the modified recycled coarse aggregate to form a dense concrete structure.
[0009] Preferably, the raw materials comprise the following components by weight: 360-390 parts of ordinary silicate cement; 1020-1080 parts of recycled coarse aggregate; 620-680 parts of natural fine sand; 16-20 parts of chemically targeted modification package; 16-19 parts of quicklime powder; 32-40 parts of inducing water; and 155-165 parts of conventional mixing water.
[0010] By adopting the above technical solution and limiting the specific weight ratio of each component, the porosity strengthening degree of recycled aggregate and the overall workability of concrete mixture are balanced, ensuring that the chemically targeted modification package fully fills the aggregate pores and avoiding the introduction of too many auxiliary materials that would interfere with the normal hydration process of ordinary Portland cement.
[0011] Preferably, the chemically targeted modification comprises the following raw materials in parts by weight: 35-45 parts of sodium tripolyphosphate, 45-55 parts of anhydrous aluminum sulfate, and 8-12 parts of sodium bicarbonate.
[0012] By adopting the above technical solution, sodium tripolyphosphate, anhydrous aluminum sulfate, and sodium bicarbonate are mixed in a specific ratio. The components enter the aggregate pores with the induced water and, under the slightly alkaline environment provided by the exothermic reaction of quicklime, the anhydrous aluminum sulfate reacts with the sodium tripolyphosphate to form a composite aluminum phosphate salt precipitate. Simultaneously, the sodium bicarbonate decomposes upon heating or reacts to release trace amounts of carbon dioxide gas. The microscopic thrust generated by this gas release drives the generated composite precipitate to compress and fill the ends of micro-cracks, forming a dense crystalline phase with micro-expansion characteristics, thereby improving the density of the recycled coarse aggregate.
[0013] Preferably, the recycled coarse aggregate is aggregate containing old mortar obtained by crushing waste building concrete; the ordinary Portland cement is P·O42.5 grade ordinary Portland cement.
[0014] By adopting the above technical solutions, the source of abandoned building solid waste and the objective existence state of old mortar are clarified, so that the porosity strengthening mechanism has a definite target; P·O42.5 grade ordinary Portland cement is used to ensure the basic mechanical support strength of the concrete matrix.
[0015] Secondly, the present invention provides a method for preparing recycled aggregate concrete using construction solid waste, employing the following technical solution: A method for preparing recycled aggregate concrete using construction solid waste includes the following steps: Dry recycled coarse aggregate and chemically targeted modification packages are fed into a forced concrete mixer for purely physical dry mixing; while the mixer is running continuously, induced water is uniformly sprayed into the mixer, and mixing continues after spraying; after the induced water is sprayed and mixing continues, quicklime powder is added into the mixer in one go without stopping, and mixing continues; after the quicklime powder is added and mixing continues, ordinary Portland cement, natural fine sand, and conventional mixing water are sequentially added into the mixer for continuous homogenization mixing, and the mixture is discharged and molded.
[0016] By adopting the above technical solution and employing a time-controlled multi-stage mixing process, the chemically targeted modification package is used to transport and in-situ activate the internal pores of the aggregate. The specific process principle is as follows: Step 1: Pure physical dry mixing allows the dry powder to adhere evenly to the surface of the recycled coarse aggregate through mechanical friction.
[0017] Step 2: Evenly spray inducing water to act as a physical carrier, allowing the powder adhering to the surface to penetrate into the interior of the dried aggregate. Control the timing of adding the inducing water to prevent the effective components from being lost to the outside of the aggregate.
[0018] Step 3: Adding quicklime powder generates an exothermic effect, accelerating the crystallization rate of the components inside the pores, while consuming excess free moisture on the surface of the aggregate.
[0019] Step 4: Add the remaining raw materials and mix. At this point, the water absorption rate of the recycled coarse aggregate has decreased significantly, ensuring the stability of the overall water-cement ratio of the concrete.
[0020] Preferably, before feeding the recycled coarse aggregate and the chemically targeted modification package into the forced concrete mixer, the method further includes a preparation step of the chemically targeted modification package: feeding sodium tripolyphosphate, anhydrous aluminum sulfate and sodium bicarbonate powder into a three-dimensional powder mixer, and continuously performing pure physical dry mixing for 15-25 minutes at a speed of 25-35 r / min under normal temperature and pressure. After discharge, the mixture is sealed and stored in a light-proof container for later use.
[0021] By adopting the above technical solution and utilizing the multi-directional motion characteristics of the three-dimensional powder mixer, it is ensured that the raw material powders of chemically targeted modification packages of different densities reach a homogeneous mixing state, preventing the effective components from localizing when entering the aggregate pores and ensuring the integrity of the precipitation and crystallization reaction within the pores.
[0022] Preferably, during the pure physical dry mixing process of the recycled coarse aggregate and the chemically targeted modification package, the spindle speed of the forced concrete mixer is controlled at 30-40 r / min, and the pure physical dry mixing time is 60-90 s; during the injection of the induced water, the induced water is uniformly sprayed into the mixer in the form of water mist particles through an atomizing spraying device, and the continued mixing time after the spraying is completed is 90-120 s.
[0023] By adopting the above technical solution, setting specific rotation speed and stirring time, the aggregate and powder are mixed evenly and the aggregate is not over-grinded and crushed. The atomized spraying method is used to make the induced water contact the aggregate in the form of tiny water droplets, preventing the concentrated water flow from washing away the modified powder on the surface of the aggregate. Combined with the set stirring time, the induced water carries the modified substances to fully penetrate into the deep layers of the aggregate.
[0024] Preferably, after adding quicklime powder, the stirring time is continued for 45-60 seconds, and during the continued stirring period after adding quicklime powder, the peak temperature of the material in the mixer is controlled to rise to within 37.1-46.1℃.
[0025] By adopting the above technical solution, the peak temperature of the material is controlled within the range of 37.1-46.1℃, providing a suitable thermal excitation environment and accelerating the crystallization and precipitation rate of the modified particles in the pores; the stirring time is limited to prevent the reactants from hardening prematurely and to avoid the negative impact of excessively high aggregate surface temperature on the subsequent hydration of ordinary Portland cement due to thermal stress.
[0026] Preferably, after adding the ordinary silicate cement, natural fine sand and conventional mixing water in sequence, the continuous homogenization mixing time is 120-150 seconds.
[0027] By adopting the above technical solution, it is ensured that ordinary silicate cement, modified recycled coarse aggregate, natural fine sand and conventional mixing water form a uniform cementitious suspension system, avoiding uneven material dispersion due to excessively short mixing time, and preventing damage to the initially formed hydration network structure due to excessively long mixing time.
[0028] This invention provides a recycled aggregate concrete prepared from construction solid waste and its preparation method. It has the following beneficial effects: This invention mixes chemically targeted modification packages with dried recycled coarse aggregate, and uses atomized induced water to directionally infiltrate sodium tripolyphosphate, anhydrous aluminum sulfate, and sodium bicarbonate powders into the micropores of old mortar. Subsequently, the exothermic hydration effect of quicklime powder is used to induce a micro-expansion crystallization precipitation reaction inside the aggregate pores, effectively filling the micro-cracks and pore defects inside the waste building concrete, transforming the originally loose recycled coarse aggregate into a dense state, and improving the physical and mechanical properties of the aggregate itself. This invention employs a multi-stage time-controlled mixing process. Before adding ordinary silicate cement and conventional mixing water, the internal pores of the aggregate are strengthened independently in the mixer, and the excess free water is consumed by quicklime. This avoids the problem of excessive absorption of mixing water by traditional recycled aggregates during mixing, which leads to a drastic loss of concrete slump. It also prevents modified components from entering the matrix and interfering with the normal hydration process of cement, ensuring that the cement gel network uniformly coats and tightly bonds the aggregate. This solution uses waste concrete fragments containing old mortar as recycled coarse aggregate, eliminating the need for energy-intensive mechanical grinding and stripping or highly polluting strong acid soaking. Through pure physical dry mixing, atomized spraying, and the synergistic effect of conventional materials, the originally wasteful and inferior aggregate is modified in situ into high-quality building structural materials. This reduces the energy consumption and process complexity of recycled aggregate pretreatment, providing an efficient and reliable technical path for the resource recycling of construction waste. Attached Figure Description
[0029] Figure 1 This is a schematic diagram showing the bar chart comparison of the intermediate water absorption rate of the recycled aggregate of the present invention; Figure 2 This is a schematic diagram of the macroscopic temperature change process of the mixed material under a specific time sequence according to the present invention. Figure 3 This is a schematic diagram showing the time-varying change of slump in freshly mixed concrete under different mix proportions and process conditions according to the present invention. Figure 4 This is a columnar schematic diagram of the compressive strength of recycled aggregate concrete at different ages under different process treatments according to the present invention; Figure 5 This is a columnar comparison diagram of the water penetration resistance depth of recycled aggregate concrete at 28 days under different process treatments according to the present invention. Detailed Implementation
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] Preparation Examples 1-3: Preparation Example 1: Weigh out 35 kg of sodium tripolyphosphate, 55 kg of anhydrous aluminum sulfate, and 10 kg of sodium bicarbonate. Add the three powdered raw materials together into a three-dimensional powder mixer. Under normal temperature and pressure, control the main shaft speed of the mixer at 30 r / min and continuously perform pure physical dry stirring for 20 min. After the powder is completely and evenly mixed, discharge the material to obtain a uniform dry powder chemically targeted modification package A1, which is then sealed and stored in the dark for later use.
[0032] Preparation Example 2: Weigh out 40 kg of sodium tripolyphosphate, 50 kg of anhydrous aluminum sulfate, and 10 kg of sodium bicarbonate. Add all three powdered raw materials to a three-dimensional powder mixer. Under normal temperature and pressure, control the mixer spindle speed at 30 r / min and continuously perform pure physical dry mixing for 20 minutes. After the powder is completely and evenly mixed, discharge the mixture to obtain a uniform dry powder chemically targeted modification package A2, which should be sealed and stored away from light for later use.
[0033] Preparation Example 3: Weigh out 45 kg of sodium tripolyphosphate, 45 kg of anhydrous aluminum sulfate, and 10 kg of sodium bicarbonate. Add all three powdered raw materials to a three-dimensional powder mixer. Under normal temperature and pressure, control the mixer spindle speed at 30 r / min and continuously perform pure physical dry mixing for 20 minutes. After the powder is completely and evenly mixed, discharge the mixture to obtain a uniform dry powder chemically targeted modification package A3, which should be sealed and stored away from light for later use.
[0034] Examples 1-3: Example
[0035] This embodiment provides a recycled aggregate concrete prepared from construction solid waste and its preparation method. The raw materials, by weight, include: 350 kg of P·O42.5 grade ordinary Portland cement, 1000 kg of recycled coarse aggregate, 600 kg of natural fine sand, 15 kg of the chemically targeted modification package A1 obtained in Preparation Example 1, 15 kg of quicklime powder, 30 kg of inducing water, and 150 kg of conventional mixing water. The preparation method includes the following steps: Step 1, solid-phase targeted loading: The dried recycled coarse aggregate and the chemically targeted modification package A1 are fed into a twin-shaft forced concrete mixer and mixed in a purely physical dry state for 60 seconds at a spindle speed of 30 r / min.
[0036] Step 2, micro-water capillary induction and inner layer penetration: While keeping the mixer running continuously, induction water is evenly sprayed into the mixer through an atomizing spray device, and mixing continues for 90 seconds after spraying.
[0037] Step 3, in-situ dehydration and thermal activation coating: After step 2 is completed, without stopping the mixer, add quicklime powder into the mixer all at once and continue mixing for 45 seconds.
[0038] Step 4, Homogeneous Mixing and Molding of the Matrix: After Step 3 is completed, ordinary Portland cement, natural fine sand and conventional mixing water are added to the mixer in sequence and continuously homogeneously mixed for 120 seconds. After the concrete mixture reaches a uniform state, it is discharged and molded according to conventional specifications. Example
[0039] This embodiment provides a recycled aggregate concrete prepared from construction solid waste and its preparation method. The raw materials, by weight, include: 375 kg of P·O42.5 grade ordinary Portland cement, 1050 kg of recycled coarse aggregate, 650 kg of natural fine sand, 18.4 kg of chemically targeted modification package A2 obtained in Preparation Example 2, 17.5 kg of quicklime powder, 36.8 kg of inducing water, and 160 kg of conventional mixing water. The preparation method includes the following steps: Step 1, solid-phase targeted loading: The dried recycled coarse aggregate and chemically targeted modification package A2 are fed into a twin-shaft forced concrete mixer and mixed in a purely physical dry state for 75 seconds at a spindle speed of 35 r / min.
[0040] Step 2, micro-water capillary induction and inner layer penetration: While keeping the mixer running continuously, induction water is evenly sprayed into the mixer through an atomizing spray device, and stirring is continued for 105 seconds after spraying.
[0041] Step 3, in-situ dehydration and thermal activation coating: After step 2 is completed, without stopping the mixer, add quicklime powder into the mixer all at once and continue mixing for 50 seconds.
[0042] Step 4, Homogeneous Mixing and Molding of the Matrix: After Step 3 is completed, ordinary Portland cement, natural fine sand and conventional mixing water are added to the mixer in sequence and continuously homogeneously mixed for 135 seconds. After the concrete mixture reaches a uniform state, it is discharged and molded according to conventional specifications. Example
[0043] This embodiment provides a recycled aggregate concrete prepared from construction solid waste and its preparation method. The raw materials, by weight, include: 400 kg of P·O42.5 grade ordinary Portland cement, 1100 kg of recycled coarse aggregate, 700 kg of natural fine sand, 22 kg of chemically targeted modified package A3 obtained in Preparation Example 3, 20 kg of quicklime powder, 44 kg of inducing water, and 170 kg of conventional mixing water. The preparation method includes the following steps: Step 1, solid-phase targeted loading: The dried recycled coarse aggregate and the chemically targeted modification package A3 are fed into a twin-shaft forced concrete mixer and mixed in a purely physical dry state for 90 seconds at a spindle speed of 40 r / min.
[0044] Step 2, micro-water capillary induction and inner layer penetration: While keeping the mixer running continuously, induction water is evenly sprayed into the mixer through an atomizing spray device, and mixing continues for 120 seconds after spraying.
[0045] Step 3, in-situ dehydration and thermal activation coating: After step 2 is completed, without stopping the mixer, add quicklime powder into the mixer all at once and continue mixing for 60 seconds.
[0046] Step 4, Homogeneous Mixing and Molding of the Matrix: After Step 3 is completed, ordinary Portland cement, natural fine sand and conventional mixing water are added to the mixer in sequence and continuously homogeneously mixed for 150 seconds. After the concrete mixture reaches a uniform state, it is discharged and molded according to conventional specifications.
[0047] Comparative Examples 1-5: Comparative Example 1: Compared with Example 2, the difference is that: this comparative example did not add chemically targeted modification package A2, quicklime powder and inducing water; in terms of preparation method, steps one to three were omitted, and recycled coarse aggregate, ordinary silicate cement, natural fine sand and 196.8 kg (i.e. the sum of inducing water and conventional mixing water in Example 2) of total mixing water were directly put into the mixer at one time, and after continuous homogenization and mixing for 135 seconds, the material was discharged and shaped. The rest are the same.
[0048] Comparative Example 2: Compared with Example 2, the difference is that: in this comparative example, 18.4 kg of chemically targeted modification package A2 was pre-dissolved in sufficient water to prepare an soaking solution, and 1050 kg of recycled coarse aggregate was placed in the soaking solution and soaked for 24 hours. The aggregate was then removed and dried at 105°C to constant weight. In terms of preparation method, steps one to three were omitted. The dried soaked modified aggregate, ordinary silicate cement, natural fine sand, quicklime powder and 196.8 kg of total mixing water were directly added into a mixer at one time and continuously homogenized for 135 seconds before being discharged and shaped. All other steps were the same.
[0049] Comparative Example 3: Compared with Example 2, the difference is that the comparative example does not use the segmented feeding sequence in the preparation method. That is, steps one to three are omitted. The recycled coarse aggregate, chemically targeted modification package A2, quicklime powder, ordinary silicate cement, natural fine sand and 196.8 kg of total mixing water are directly put into the mixer at one time, and the mixture is continuously homogenized and stirred for 135 seconds before being discharged and shaped. The rest are the same.
[0050] Comparative Example 4: Compared with Example 2, the difference is that: no quicklime powder was added to the raw materials for this comparative example; in terms of preparation method, step three (in-situ dehydration and thermal activation coating) was omitted, that is, after the micro water capillary induction in step two, ordinary silicate cement, natural fine sand and conventional mixing water were directly added to the mixer in sequence, and after continuous homogenization and mixing for 135 seconds, the material was discharged and shaped. The rest are the same.
[0051] Comparative Example 5: Compared with Example 2, the difference is that: no chemically targeted modification package A2 was added to the raw materials for this comparative example; in terms of preparation method, in step one, only the dried recycled coarse aggregate was put into the mixer and mixed for 75 seconds, and then steps two, three and four were carried out in sequence, and the rest were the same.
[0052] Test Examples 1-5: Test Example 1: The following is an experimental test description and data analysis of the intermediate water absorption rate of aggregates: In the preparation process of Examples 1 to 3 and Comparative Examples 4 to 5, at the end of step three and before cement and conventional mixing water were added, the mixer was stopped and 500g of recycled aggregate was sampled from the mixer. At the same time, untreated original recycled coarse aggregate was reserved as a baseline control group.
[0053] The extracted aggregate sample was placed in a standard sieve with a aperture of 4.75 mm and sieved under dry conditions to remove loose free powder adhering to the surface of the aggregate.
[0054] The sieved aggregate samples were placed in a forced-air drying oven and dried at 105±5℃ to constant weight. After being removed and cooled to room temperature in a desiccator, their dry mass was weighed.
[0055] The dried aggregate sample was completely immersed in pure water at 20±2℃ and left to soak for 24 hours.
[0056] Remove the soaked aggregate and wipe off the free water on the surface of the aggregate with a wrung-out damp towel until it reaches a saturated surface-dry state. Weigh its saturated surface-dry mass.
[0057] The water absorption rate of each aggregate sample group was calculated based on the percentage of the difference between the saturated surface dry mass and the dry mass to the dry mass.
[0058] Table 1. Test data on intermediate water absorption rate of recycled aggregate. Sample Name Dry mass (g) Saturated dry surface mass (g) Water absorption rate (%) Untreated aggregate 486.2 521.4 7.24 Example 1 491.5 509.3 3.62 Example 2 488.7 504.1 3.15 Example 3 493.1 507.3 2.88 Comparative Example 4 485.6 515.1 6.07 Comparative Example 5 489.3 522.8 6.84 in conclusion: Figure 1 The figure shows a bar chart comparing the intermediate water absorption rates of recycled aggregates. The chart shows the macroscopic differences in water absorption rates of untreated aggregates, aggregates treated with the method of the present invention in Examples 1 to 3, and aggregates in Comparative Examples 4 and 5 under treatment lacking specific components.
[0059] According to the data in Table 1, the water absorption rate of the untreated recycled aggregate reached 7.24%, reflecting the high porosity characteristics of the waste concrete mortar. The water absorption rates of Examples 1 to 3 ranged from 2.88% to 3.62%, showing a decrease compared to the untreated state. Combined with... Figure 1 As can be seen, this scheme utilizes capillary negative pressure in the micro-water induction stage to draw sodium tripolyphosphate and anhydrous aluminum sulfate solution into the deep layers of the aggregate. Combined with the subsequent addition of quicklime powder, a hydration and dehydration reaction occurs on the surface of the aggregate. The quicklime rapidly consumes surface moisture and forms a physical barrier layer. Simultaneously, its exothermic hydration process raises the temperature inside the aggregate pores, causing sodium bicarbonate to decompose and generate gas. The resulting gas pressure pushes the aluminum sulfate reaction solution into the micro-capillaries, accelerating crystallization and precipitation under thermal excitation. The precipitate fills the original pore network, thereby macroscopically reducing the water adsorption capacity of the recycled aggregate.
[0060] Comparative Example 4, without the addition of quicklime powder, had a water absorption rate of 6.07%. The lack of quicklime prevented the formation of a rapid dehydration and sealing layer on the aggregate surface, and the reaction system lacked the heating conditions required for hydration heat activation. Chemicals such as aluminum sulfate introduced into the pores by micro-water underwent reverse seepage during the immersion test, failing to rapidly form a dense solid filler deep within the pores, and the pore channels of the old mortar were not effectively closed.
[0061] Comparative Example 5, without the addition of a chemically targeted modification package, had a water absorption rate of 6.84%. Although quicklime was added to the system to absorb surface moisture, the deep capillary structure remained essentially unchanged due to the lack of inorganic salt raw materials for in-situ precipitation reactions within the aggregate pores. During the test, the calcium hydroxide powder adhering to the surface dissolved, allowing moisture to re-enter the internal pores. The discrepancy between the results of the examples and the comparative examples demonstrates a technical connection between the physical timing control and multiphase chemical precipitation of this invention; densification of the internal structure of recycled aggregate cannot be achieved solely through moisture control or the addition of a single material.
[0062] Test Example 2: The following is an experimental test description and data analysis of macroscopic temperature history monitoring during the mixing process: Install armored thermocouple temperature probes in the non-interference area inside the twin-shaft forced concrete mixer. Adjust the probe position to a depth that allows stable contact with the mixture, and connect the probe wires to a multi-channel data acquisition instrument.
[0063] The test environment temperature was set to be constant at 20±1℃ to reduce the interference of ambient temperature difference on the test results.
[0064] The test time zero point is set as the starting time of step three (adding quicklime powder) in the preparation process of each embodiment and comparative example; for the comparative example without segmented feeding or without adding quicklime, the time zero point is the moment when conventional mixing water and cement are added for the main mixing.
[0065] Turn on the data acquisition instrument, set the sampling frequency to record temperature data every 2 seconds, continuously monitor and record the temperature change of the material in the mixer, and record for a total duration of 120 seconds.
[0066] After the test, the data was exported from the data acquisition instrument, and the temperature values at the 0s, 15s, 30s, 45s, 60s, 90s and 120s nodes were extracted and summarized.
[0067] Table 2. Macroscopic Temperature Test Data of Materials During Mixing Process Test time (s) Example 1 (°C) Example 2 (°C) Example 3 (°C) Comparative Example 1 (°C) Comparative Example 4 (°C) 0 20.4 20.6 20.3 20.5 20.2 15 26.7 29.1 31.5 20.7 20.4 30 34.2 38.5 41.8 21.1 20.5 45 36.8 41.3 45.4 21.4 20.6 60 37.1 41.6 46.1 21.6 20.7 90 35.5 40.2 44.5 21.8 20.8 120 34.2 38.7 42.1 22.0 20.9 in conclusion: Figure 2 The graph shows the macroscopic temperature change of the mixed materials over a specific time period. The horizontal axis represents the recording time, and the vertical axis represents the material temperature. It records the temperature response trends of Examples 1 to 3, as well as Comparative Examples 1 and 4, in the initial stage of mixing.
[0068] Based on the data in Table 2, combined with Figure 1 In Examples 1 to 3, the macroscopic temperature of the material showed a significant upward trend within the time period from 0s to 60s, with peak temperatures reaching 37.1℃, 41.6℃, and 46.1℃, respectively. Combined with... Figure 2 The curve characteristics show that after feeding in step three, the quicklime powder and the free induced water introduced in step two on the surface of the recycled aggregate underwent a rapid hydration reaction. This exothermic reaction released a large amount of heat energy in a short time, causing the overall temperature of the material group in the mixer to jump. The heat entered the porous system inside the recycled aggregate through solid-phase conduction, providing activation energy for the chemically targeted modified components already absorbed into the pores. The temperature increase promoted the endothermic decomposition of sodium bicarbonate, which released carbon dioxide gas; since the surface of the aggregate had been dehydrated by quicklime to form a physical sealing layer, the gas generated inside could not escape, resulting in an increase in pressure inside the pores. This pressure gradient forced the free liquid phase containing anhydrous aluminum sulfate to seep into the capillaries with smaller pore sizes. With the thermal activation effect, the precipitation and crystallization rate of free calcium ions and aluminum sulfate accelerated, and the in-situ generated crystals completed network filling in the deep layers of the aggregate.
[0069] Comparative Example 1 used a traditional one-time feeding and mixing process, and its system temperature rose slightly from 20.5℃ to 22.0℃; Comparative Example 4 used a segmented induction process but lacked quicklime, and its system temperature remained between 20.2℃ and 20.9℃. The curves for these two sets of data are shown in... Figure 2 The results showed that the early hydration heat release rate of conventional silicate cement was low, and coupled with the influence of the specific heat capacity of a large amount of conventional mixing water, the system could not provide effective thermal activation conditions within 120 seconds. The lack of quicklime not only meant the inability to form a dehydration sealing shell on the surface, but also resulted in the system remaining at room temperature, causing the aluminum sulfate precipitation reaction inside the pores to progress slowly due to insufficient activation energy. When conventional mixing water and a large amount of cement were subsequently added, the lack of a pre-densification crystallization layer led to the reverse dissolution and leaching of incompletely reacted chemical reagents, ultimately resulting in the failure of aggregate modification. The test data objectively confirmed the technical necessity of the spatiotemporal linkage mechanism between quicklime dehydration heat release and internal chemical reactions for achieving aggregate strengthening.
[0070] Test Example 3: The following are the experimental test results and data analysis for the workability of freshly mixed concrete: The experimental environment temperature was controlled at 20±2℃, and the relative humidity was greater than 50%. A standard slump cone was prepared and its inner wall was wiped with a damp cloth. It was then placed stably on a hard, non-absorbent horizontal base.
[0071] Discharge the freshly mixed concrete mixture from the mixer. Fill the slump cone with the mixture in three layers, each layer filling to a height of about one-third of the cone's height. After each layer is filled, use a standard tamping rod to tamp the mixture evenly in a spiral motion from the edge to the center 25 times. The tamping rod should penetrate the entire bottom layer, while the tamping rod should penetrate about 20mm into the bottom layer for the middle and top layers.
[0072] After the top layer of concrete has been tamped, use a trowel to scrape the excess concrete mixture along the opening of the cylinder and remove the concrete around the bottom of the cylinder.
[0073] Lift the slump cone vertically and smoothly upwards, completing the lifting process within 5 to 10 seconds. Measure the height difference between the cone height and the highest point of the slumped concrete specimen; this value is the initial (0 min) slump of the concrete.
[0074] Place the remaining concrete mixture into a sealed container or cover it with a damp cloth and let it stand. After standing for 30 minutes and 60 minutes, remove the mixture, stir it again with a shovel, and test its slump again following the same steps. Record the slump data over time.
[0075] Table 3. Slump and time-lapse test data of fresh concrete mixture. Test sample Initial slump (mm) 30-minute slump (mm) 60-minute slump (mm) Example 1 186 171 155 Example 2 194 182 164 Example 3 197 188 172 Comparative Example 1 182 141 108 Comparative Example 3 146 114 87 in conclusion: Figure 3 This is a line graph comparing the changes in slump of fresh concrete over time under different mix proportions and process conditions. The horizontal axis represents the test settling time, and the vertical axis represents the measured slump value, showing the differences in workability retention between Examples 1 to 3 and Comparative Examples 1 and 3.
[0076] Based on the data in Table 3, combined with Figure 3 The initial slump of Examples 1 to 3 ranged from 186 mm to 197 mm, and remained between 155 mm and 172 mm after 60 minutes, showing a relatively small overall slump loss. The fresh concrete exhibited good workability and fluidity retention. During the preparation process of these examples, sodium tripolyphosphate and anhydrous aluminum sulfate entered the pores of the recycled aggregate under micro-water induction. Subsequently, quicklime was added and underwent a hydration reaction, forming a dense, dehydrated physical barrier layer on the aggregate surface. This segmented pretreatment altered the water exchange channels in the aggregate pore network. When conventional mixing water and silicate cement were added during the main mixing stage, the pores inside the aggregate were already physically sealed and chemically filled, preventing the absorption of free water from the external fresh slurry by the pores of the old mortar. The silicate cement achieved a stable water-cement ratio environment in the early stages of hydration, allowing free water in the slurry to remain on the outside of the cement particles for a long time, providing lubrication. Macroscopically, this resulted in minimal slump loss of the mixture over time.
[0077] Comparative Example 1 used untreated recycled aggregate for conventional mixing, with an initial slump of 182 mm, but the slump dropped sharply to 108 mm after 60 minutes. The unsealed porous recycled aggregate continuously absorbed free water from the cement paste during mixing and settling. Over time, the water-cement ratio of the cement paste decreased, and the friction between solid particles increased, causing the concrete to dry rapidly and lose its fluidity.
[0078] Comparative Example 3 involved a one-time mixing of all raw materials, including quicklime and chemically targeted modifiers. The initial slump was only 146 mm, dropping to 87 mm after 60 minutes, completely losing its pumpability and workability. In this one-time mixing system, quicklime directly contacted and reacted rapidly with conventional mixing water, consuming a large amount of free water. Furthermore, sodium tripolyphosphate and anhydrous aluminum sulfate dissolved in the main aqueous phase and were uniformly dispersed within the cement paste, failing to penetrate the deep pores of the aggregate. Aluminum sulfate rapidly formed flocculated sediment in the external paste, significantly increasing the paste viscosity and leading to severe deterioration of the initial workability of the concrete. The test data from the two comparative examples conversely confirmed that the process design of this invention, through micro-water timing control and in-situ coating and retention, ensured the strengthening effect of recycled aggregates while avoiding negative interference of modified materials on the macroscopic rheological properties of the new cement matrix, thus verifying the technical reliability of this spatiotemporal isolation mechanism.
[0079] Test Example 4: The following are the experimental test results and data analysis for macroscopic mechanical properties (compressive strength): Prepare a standard steel test mold with an inner diameter of 150mm×150mm×150mm, clean the inner wall and apply a thin layer of release agent evenly to the surface.
[0080] The freshly produced concrete mixtures prepared in each embodiment and comparative example were placed into the mold in two layers, with the thickness of each layer controlled to be about half the height of the mold.
[0081] Securely fix the filled mold to the test vibration table, turn on the vibration table to compact the concrete until cement paste appears on the concrete surface and obvious air bubbles stop escaping.
[0082] After the vibration stops, use a metal trowel to scrape off the excess concrete mixture from the top of the mold, smooth the surface along the edge of the mold, and cover the surface of the specimen with a plastic film to prevent moisture from evaporating too quickly.
[0083] The molded specimens were placed in an environment at 20±5℃ and allowed to stand for 24 hours. After standing, the specimens were demolded and the corresponding group and preparation date were marked on the surface of each specimen.
[0084] The demolded specimens were immediately transferred to a standard constant temperature and humidity curing room with a temperature controlled at 20±2℃ and a relative humidity maintained at over 95% for curing.
[0085] When the specimens have reached the specified curing periods of 3 days, 7 days and 28 days, the corresponding specimens are taken out of the curing room and the free moisture on the surface of the specimens is wiped off with a dry towel.
[0086] Place the specimen stably at the center of the lower bearing plate of the microcomputer-controlled electro-hydraulic servo universal pressure testing machine, ensuring that the bearing surface of the specimen is perpendicular to the top surface during molding.
[0087] Start the testing machine and apply axial compressive load to the specimen continuously and uniformly at a loading rate of 0.5 to 0.8 MPa per second until the specimen fails. Record the ultimate failure load displayed by the equipment and calculate the compressive strength value of each specimen based on the compressed area.
[0088] Table 4. Test data of compressive strength of concrete at different ages Test sample 3-day compressive strength (MPa) 7-day compressive strength (MPa) 28-day compressive strength (MPa) Example 1 24.3 33.6 46.2 Example 2 26.8 36.1 49.7 Example 3 27.5 37.4 51.3 Comparative Example 1 18.2 26.5 35.8 Comparative Example 3 15.6 23.4 31.2 Comparative Example 4 20.1 28.7 39.4 Comparative Example 5 19.3 27.2 36.5 in conclusion: Figure 4 This is a bar chart showing the compressive strength of recycled aggregate concrete at different ages under different processing techniques. The horizontal axis represents the group name of each example and comparative example, and the vertical axis represents the measured compressive strength value. The bars with different shades of gray correspond to curing ages of 3 days, 7 days, and 28 days, respectively.
[0089] Based on the data in Table 4, combined with Figure 4 The early strength at 3 days in Examples 1 to 3 reached 24.3 to 27.5 MPa, and the final strength at 28 days ranged from 46.2 to 51.3 MPa. These data reflect that the preparation process of this invention exhibits strength gains throughout the entire concrete hardening cycle. During the preparation process, sodium tripolyphosphate and anhydrous aluminum sulfate penetrate deep into the porous old mortar of the recycled aggregate during the micro-water induction stage. Subsequently, quicklime is added to initiate dehydration, sealing, and hydration exothermic reactions. The heat of hydration stimulates the crystallization and precipitation reaction of aluminum sulfate deep within the pores. The resulting precipitate fills the microcracks and pore network of the old mortar from the inside, improving the matrix strength of the recycled aggregate itself. Simultaneously, the calcium hydroxide coating layer formed by the dehydration of quicklime on the outer surface of the aggregate provides highly active calcium-rich crystal nuclei for the subsequently added silicate cement. The CSH gel generated by the hydration of silicate cement attaches and grows from these crystal nuclei, forming a continuous chemical bond between the new cement paste and the surface of the old aggregate, thoroughly improving the density of the interfacial transition zone (ITZ).
[0090] Comparative Example 1, using untreated recycled aggregate in conventional mixing, achieved a 28-day strength of only 35.8 MPa. The high porosity of the untreated recycled aggregate made it highly susceptible to stress concentration and fracture at the old mortar layer under pressure, and the bonding between the new and old mortar interfaces was weak. Comparative Example 3, using a single-stage mixing process, achieved a 28-day strength as low as 31.2 MPa. The chemical modifiers failed to penetrate the deep layers of the aggregate, instead flocculating in the external slurry, interfering with the normal hydration process of silicate cement and resulting in a loose overall matrix structure. Comparative Example 4, lacking quicklime, achieved a 28-day strength of 39.4 MPa. Due to the lack of surface physical sealing and thermal activation, the chemical substances that entered the pores underwent reverse seepage during the main mixing stage, and the precipitation reaction failed to seal micro-cracks, significantly reducing the strengthening effect on the internal structure of the aggregate. Comparative Example 5, without the addition of a chemical modifier packet, achieved a 28-day strength of 36.5 MPa, indicating that the water absorption effect of quicklime on the aggregate surface alone could not compensate for the inherent defects deep within the aggregate. Comprehensive mechanical test data have verified that the spatial linkage mechanism formed by micro-water induction, deep sedimentation and surface thermal activation sealing is the technical basis for achieving a leap in the mechanical properties of recycled aggregate concrete.
[0091] Test Example 5: The following is an experimental test description and data analysis of the water permeability resistance of concrete: The prepared concrete mixture was filled into a standard truncated conical impermeable test mold according to the mix proportions. The inner diameter of the top surface of the mold was 175 mm, the inner diameter of the bottom surface was 185 mm, and the height was 150 mm. The mixture was compacted using a mechanical vibrating table and demolded after standing for 24 hours.
[0092] After demolding, the specimens were placed in a standard curing room with a temperature of 20±2℃ and a relative humidity of over 95% and cured for 28 days. The specimens were then removed and allowed to air dry in an indoor environment.
[0093] Use a wire brush to remove the cement slurry from both ends of the specimen. Apply a layer of heated and melted paraffin wax and rosin mixture sealant evenly to the side surface of the specimen, and quickly press it into the preheated metal mold of the permeability tester using a screw press to complete the lateral sealing.
[0094] The mold containing the specimen was installed on the fully automatic concrete permeability tester, and the equipment was started to apply water pressure from the bottom of the specimen. The initial water pressure was set to 0.1 MPa, and then the water pressure was increased by 0.1 MPa every 8 hours until a constant test pressure of 1.2 MPa was reached.
[0095] The specimen was kept under a water pressure of 1.2 MPa for 24 hours, during which time the top surface of the specimen was observed for any water seepage. After the pressurization stage, the permeability tester was turned off, the water pressure was released, and the specimen was removed along with the mold and ejected using a demolding machine.
[0096] The tested specimen was placed under a microcomputer-controlled electro-hydraulic servo pressure testing machine, and a splitting load was applied along the diameter of the specimen to divide it into two.
[0097] On the fractured surface, use a steel ruler to measure the depth of water penetration along the bottom surface of the specimen. Select 10 measurement points at equal intervals along the transverse direction of the specimen, record the water penetration depth at each point, and take the arithmetic mean of the values at these 10 points as the average water penetration depth of the specimen, and record the maximum water penetration depth.
[0098] Table 5. Test data on water penetration depth of concrete at 28 days old. Test sample Maximum seepage depth (mm) Average seepage depth (mm) Example 1 17.4 12.8 Example 2 15.2 10.5 Example 3 14.8 11.3 Comparative Example 1 56.7 42.1 Comparative Example 3 68.2 51.4 Comparative Example 4 39.5 28.7 Comparative Example 5 43.1 32.5 in conclusion: Figure 5 This is a bar chart comparing the water penetration depth of recycled aggregate concrete at 28 days of age under different processing methods. The horizontal axis represents the test group for each example and comparative example, and the vertical axis represents the measured water penetration height. Dark gray bars represent the average water penetration depth, and light gray bars represent the maximum water penetration depth at the measuring points.
[0099] Based on the data in Table 5, combined with Figure 5 In Examples 1 to 3, the average water penetration depth was controlled within the range of 10.5 mm to 12.8 mm, with the maximum water penetration depth not exceeding 17.4 mm. Test results show that the internal pore structure of the system in these examples is dense, exhibiting high resistance to pressurized water penetration. In the preparation process, micro-water capillary induction allows sodium tripolyphosphate and anhydrous aluminum sulfate to penetrate the porous old mortar deep within the recycled aggregate. After quicklime is added, it absorbs free water from the aggregate surface and undergoes an exothermic reaction, generating a dehydrated coating layer that seals the pore channels. The carbon dioxide gas generated by the thermal decomposition of sodium bicarbonate establishes positive pressure internally, pushing aluminum sulfate into the micropores and accelerating in-situ crystallization and precipitation. The generated precipitate blocks the inherent capillary seepage channels of the old aggregate. Simultaneously, the calcium hydroxide-rich layer generated on the aggregate surface provides homogeneous crystal nucleation points for subsequent silicate cement hydration, resulting in a dense coverage of the new and old interface transition zone by the generated hydrated calcium silicate gel. Micropore filling and interfacial chemical bonding eliminate the macroscopically interconnected water penetration network.
[0100] Comparative Example 1, using untreated recycled aggregate, achieved an average water penetration depth of 42.1 mm and a maximum penetration depth of 56.7 mm. The surface of the old mortar formed from the crushed waste concrete was loose and had well-developed microcracks, directly becoming a physical shortcut for pressurized water seepage without excessive treatment. Comparative Example 3, using a one-time mixing of all raw materials, achieved an average water penetration depth as high as 51.4 mm. The chemical targeting substances were diluted and distributed within the slurry during the addition of water to the main body, failing to penetrate deep into the aggregate to repair defects. Simultaneously, external flocculants hindered the homogeneous formation of the normal cement paste, resulting in a loose and interconnected matrix interface after molding. Comparative Example 4, lacking quicklime powder, had an average water penetration depth of 28.7 mm. The lack of surface dehydration and thermal activation conditions caused reverse osmosis leaching of internal aggregate chemicals upon the addition of conventional mixing water, preventing the formation of stable sediment fillers on the deep capillary pore walls. The water penetration depth test directly confirmed the physicochemical blocking effect of micro-water induced infiltration combined with in-situ thermal activation sealing on the closure of the microporous network within concrete.
Claims
1. A type of recycled aggregate concrete prepared using construction solid waste, characterized in that, Including the following parts by weight of raw materials: 350-400 parts of ordinary Portland cement; 1000-1100 parts of recycled coarse aggregate; 600-700 parts of natural fine sand; 15-22 portions of chemically targeted modification package; 15-20 parts quicklime powder; Inducing water 30-44 parts; Use 150-170 parts of regular mixing water.
2. The recycled aggregate concrete prepared from construction solid waste according to claim 1, characterized in that, The raw materials comprise the following components in parts by weight: 360-390 parts of ordinary Portland cement; 1020-1080 parts of recycled coarse aggregate; 620-680 parts of natural fine sand; 16-20 portions of chemically targeted modification package; 16-19 parts quicklime powder; Inducing water 32-40 parts; Use 155-165 parts of regular mixing water.
3. The recycled aggregate concrete prepared from construction solid waste according to claim 1, characterized in that, The chemical targeted modification includes the following raw materials in parts by weight: 35-45 parts sodium tripolyphosphate, 45-55 parts anhydrous aluminum sulfate, and 8-12 parts sodium bicarbonate.
4. The recycled aggregate concrete prepared using construction solid waste according to claim 1, characterized by, The recycled coarse aggregate is an aggregate containing old mortar obtained by crushing waste building concrete.
5. The recycled aggregate concrete prepared using construction solid waste according to claim 1, characterized by, The ordinary silicate cement is P·O42.5 grade ordinary silicate cement.
6. A method of producing recycled aggregate concrete using construction waste according to any one of claims 1 to 5, characterized in that, Includes the following steps: The dried recycled coarse aggregate and the chemically targeted modification package are fed into a forced concrete mixer for pure physical dry mixing. While keeping the mixer running, spray the inducing water evenly into the mixer, and continue mixing after spraying. After the inducing water has been sprayed in and stirring has continued, do not stop the mixer. Add quicklime powder into the mixer all at once and continue stirring. After adding quicklime powder and continuing to stir, ordinary silicate cement, natural fine sand and conventional mixing water are added to the mixer in sequence for continuous homogenization and stirring. The mixture is then discharged and molded.
7. The preparation method according to claim 6, characterized in that, Before feeding the recycled coarse aggregate and the chemically targeted modification package into a forced concrete mixer, the process also includes a pre-preparation step of the chemically targeted modification package: Sodium tripolyphosphate, anhydrous aluminum sulfate, and sodium bicarbonate powder are put into a three-dimensional powder mixer. Under normal temperature and pressure, the main shaft speed of the mixer is controlled at 25-35 r / min for continuous pure physical dry stirring for 15-25 min. After discharge, the mixture is sealed and stored in the dark for later use.
8. The preparation method according to claim 6, characterized in that, During the pure physical dry mixing process of the recycled coarse aggregate and the chemically targeted modification package, the spindle speed of the forced concrete mixer is controlled at 30-40 r / min, and the pure physical dry mixing time is 60-90 s. During the process of spraying the inducing water, the inducing water is evenly sprayed into the mixer in the form of water mist particles through an atomizing spraying device, and the stirring time after the spraying is completed is 90-120 seconds.
9. The preparation method according to claim 6, characterized in that, After adding quicklime powder, continue stirring for 45-60 seconds, and during the continued stirring period after adding quicklime powder, control the peak temperature of the material in the mixer to rise to within 37.1-46.1℃.
10. The method of claim 6, wherein, After adding the ordinary silicate cement, natural fine sand and conventional mixing water in sequence, the continuous homogenization mixing time is 120-150 seconds.